1997
DOI: 10.1590/s0100-879x1997000700005
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharidase levels in normal epithelium of the small intestine of rats with iron-deficiency anemia

Abstract: Iron-deficiency anemia is the nutritional deficiency most frequently occurring throughout the world, which manifests as a complex systemic disease involving all cells, affecting enzyme activities and modifying protein synthesis. In view of these considerations, the objective of the present study was to determine the effects of irondeficiency anemia on disaccharidases and on the epithelial morphokinetics of the jejunal mucosa. Newly weaned male Wistar rats were divided into 4 groups of 10 animals each: C6w rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
6
20
0
Order By: Relevance
“…In agreement with previous studies, it was observed that iron-deficient Wistar rats have significantly lower sucrase and lactase activities compared with their control littermates (2,4,5,9,16,20,31,38). This decreased activity cannot be attributable to changes in kinetic properties of the enzymes as evidenced by no significant differences in K m values, inferring that it is primarily due to reduced quantities of the enzyme present in the mucosa.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with previous studies, it was observed that iron-deficient Wistar rats have significantly lower sucrase and lactase activities compared with their control littermates (2,4,5,9,16,20,31,38). This decreased activity cannot be attributable to changes in kinetic properties of the enzymes as evidenced by no significant differences in K m values, inferring that it is primarily due to reduced quantities of the enzyme present in the mucosa.…”
Section: Discussionsupporting
confidence: 90%
“…The enzymatic activity of each individual disaccharidase is influenced primarily by the dietary level of their corresponding substrate (2, 12), and, under normal conditions, this level of activity is controlled by the abundance of the mRNA encoding the proteins (12, 34). However, it has been shown on many occasions that dietary iron deficiency can cause a significant decrease in disaccharidase activity (2,4,5,9,16,20,31,38) and that this decrease is reversible by iron supplementation (9,20,38).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The epithelium of the small intestine is continuously and rapidly renewed in a process involving cell generation and migration from the multi-potential stem cells, housed in specific "niches" within the crypts, to the extrusion of the terminally differentiated cells at the tips of the villi, within a period of 3-5 days (24). HIEC play a central role in absorptive and secretory functions, protecting the organisms from bacteria and toxins, providing an effective barrier against the complex antigenic load of intestinal contents (3,25).…”
Section: Discussionmentioning
confidence: 99%